Tahapan Misi Pemuridan: Sebuah Usulan Kepada Guru PAK Berdasarkan Eksegesis Injil Matius 4:18-22 - Karlau, Sensius Amon (STT Arastamar Wamena, 2024)
This research discusses the mission of discipleship based on the interpretation of the Gospel of Matthew chapter 4:18-22. Apparently, a number of learning activities by PAK teachers emphasize increasing cognitive aspects without balancing it with the mission of discipleship. This problem then demands that PAK praxis should not be limited to formal-theoretical motives. Ironically, the emphasis on rigid and boring theoretical aspects also distorts the fundamental intent of the discipleship mandate as Jesus did in the initial story of the calling of His disciples. An in-depth study of this topic starts from the hermeneutic method, accompanied by a bibliographic approach that leads to the study of the theological, social, context and lexical analysis of the text of the Gospel of Matthew 4:18-22. So it was found that Jesus' mission of discipleship was constructed universally, urgently and continuously. Therefore, the intensity of the mission of discipleship should be articulated through various stages initiated through the act of seeking, calling and committing to becoming an exemplary figure. This is the stage of the discipleship mission that can be implemented by every PAK teacher until the realization of a student's personal relationship with Jesus as Teacher, Lord and personal Savior in the guarantee of God the Father's inclusion.